2018
DOI: 10.1111/mec.14713
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity and evolutionary divergence in gene expression associated with alternative habitat use in larvae of the European Fire Salamander

Abstract: Transcriptomes of organisms reveal differentiation associated with the use of different habitats. However, this leaves open how much of the observed differentiation can be attributed to genetic differences or to transcriptional plasticity. In this study, we disentangle causes of differential gene expression in larvae of the European fire salamander from the Kottenforst forest in Germany. Larvae inhabit permanent streams and ephemeral ponds and represent an example of a young evolutionary split associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 60 publications
4
11
0
Order By: Relevance
“…The higher baseline expression of environmentally responsive genes noted in these studies might represent an evolved response to a frequently encountered stress, allowing these populations to maintain tolerance in the absence of an acclimatization response. Overlaps between the genetic basis of plasticity and population divergence have also been observed in European fire salamanders, Salamandra salamandra [106], grayling Thymallus thymallus [107] and wall lizards P. muralis [85].…”
Section: Genomic Datamentioning
confidence: 87%
“…The higher baseline expression of environmentally responsive genes noted in these studies might represent an evolved response to a frequently encountered stress, allowing these populations to maintain tolerance in the absence of an acclimatization response. Overlaps between the genetic basis of plasticity and population divergence have also been observed in European fire salamanders, Salamandra salamandra [106], grayling Thymallus thymallus [107] and wall lizards P. muralis [85].…”
Section: Genomic Datamentioning
confidence: 87%
“…Genomic studies along environmental gradients in amphibians are slowly starting to accumulate (Bonin et al, ; Czypionka et al, ; Guo et al, ; Pastenes et al, ; Yang et al, ). Guo et al () used pooled RAD‐seq and showed genomic adaptive divergence among Bufo andrewsi populations along an altitudinal gradient on the Tibetan plateau, identifying candidate SNPs located in genes that may be involved in high‐altitude adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…In amphibians, several studies have found phenotypic evidence for adaptive divergence and counter‐gradient variation along wide environmental gradients, highlighting the importance of growing season length as a selective factor (e.g., Berven, ; Berven, Gill, & Smith‐Gill, ; Laugen, Laurila, Räsänen, & Merilä, ; Luquet, Léna, Miaud, & Plénet, ; Muir, Biek, Thomas, & Mable, ; Palo et al, ). However, until recently, population genomic studies investigating adaptive variation along environmental gradients in amphibians have been relatively scarce (but see Bonin, Taberlet, Miaud, & Pompanon, ; Czypionka, Goedbloed, Steinfartz, & Nolte, ; Guo, Lu, Liao, & Merilä, ; Pastenes et al, ; Yang, Qi, & Fu, ), and no studies, to our knowledge, have focused on genomic divergence along latitudinal gradients, probably reflecting the general scarcity of genomic resources for amphibians (but see Hammond et al, ; Hellsten et al, ; Session et al, ; Shu, Laurila, Suter, & Räsänen, ; Sun et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In such a time series, samples during the early stages of an evolutionary sequence may be useful in distinguishing between PLE and mutation-driven evolution (Levis & Pfennig, 2019b). For example, one could demonstrate greater environmental sensitivity of ancestral alleles compared to derived ones (e.g., Corl et al, 2018;Parsons et al, 2016) and/or use comparisons among outgroups or ancestors and descendants to evaluate divergence in environmental sensitivity in gene regulation or expression (e.g., Czypionka, Goedbloed, Steinfartz, & Nolte, 2018;Koch et al, 2017). These genetic tests would also require additional evidence that there was ancestral plasticity before fixation of a particular phenotype, and this evidence of ancestral plasticity might take many forms.…”
Section: Suggestions For Future Researchmentioning
confidence: 99%
“…These genetic tests would also require additional evidence that there was ancestral plasticity before fixation of a particular phenotype, and this evidence of ancestral plasticity might take many forms. For example, one could demonstrate greater environmental sensitivity of ancestral alleles compared to derived ones (e.g., Corl et al, 2018;Parsons et al, 2016) and/or use comparisons among outgroups or ancestors and descendants to evaluate divergence in environmental sensitivity in gene regulation or expression (e.g., Czypionka, Goedbloed, Steinfartz, & Nolte, 2018;Koch et al, 2017).…”
Section: Suggestions For Future Researchmentioning
confidence: 99%